Curcumin-loaded composite emulsion gel and preparation method and application thereof

CN122954151APending Publication Date: 2026-10-23GUANGDONG OCEAN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611146961.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0008]针对现有技术中,TMP/κCOS纳米复合物在包载姜黄素时包封率有限,无法充分改善姜黄素光热稳定性差、口服生物利用度低的固有缺陷;同时传统乳液凝胶制备多需酸、碱、酶或离子诱导,反应条件严苛,易造成包埋活性物质的损失,且缺乏将该现有纳米复合物与特定油相复合构建高效姜黄素递送体系的相关研究,无法充分发挥该纳米复合物的应用潜力,罗非鱼精深加工的应用场景仍有待拓展

Benefits of technology

本发明基于现有公开的TMP/κCOS纳米复合物,通过与特定油相复合构建乳液凝胶体系,可实现姜黄素的更高效率包载,姜黄素包封率可达到90%以上,显著高于单纯使用该纳米复合物时的包载效果,可进一步提升姜黄素的包载效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122954151A_ABST
    Figure CN122954151A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of delivery carriers, and discloses a curcumin-loaded composite emulsion gel as well as a preparation method and application thereof. A TMP / κCOS nanocomposite prepared from tilapia muscle protein (TMP) and kappa-carrageenan oligosaccharide (κCOS) is used as an aqueous phase, an oil phase in which curcumin (CUR) is dissolved is added, and the composite emulsion gel is prepared through one-step high-speed shearing treatment. The system can efficiently load curcumin, and the encapsulation efficiency is not less than 90%. The system can improve the storage, photothermal stability of curcumin, improve the bioavailability of curcumin in the in-vitro digestion process, expand the application scenarios of the TMP / κCOS nanocomposite, and provide technical support for efficient delivery of fat-soluble active substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of delivery carrier technology, and relates to a composite emulsion gel encapsulating curcumin, its preparation method and application. Background Technology

[0002] Curcumin is a natural polyphenolic compound extracted from plants of the genus Curcuma in the ginger family (Zingiberaceae). It possesses various biological activities, including antioxidant, anti-inflammatory, and anti-tumor effects, and has high application potential in functional foods and pharmaceuticals. However, curcumin itself has inherent defects: it is highly hydrophobic, has extremely poor water solubility, and its molecular structure is highly sensitive to light, heat, and pH. In neutral to alkaline physiological environments, it is prone to hydrolysis and oxidative degradation, resulting in insufficient oral bioavailability of free curcumin, which severely restricts its practical application.

[0003] To address the aforementioned issues, various curcumin delivery systems have been developed to improve the dispersibility, stability, and bioavailability of curcumin. Lipid-based delivery systems, such as liposomes and nanoemulsions, utilize the hydrophobicity of curcumin to encapsulate it within lipid structures, improving its dispersibility to some extent. However, liposomes suffer from vesicle aggregation and leakage of active substances, resulting in poor long-term storage stability. Ordinary nanoemulsions often rely on high concentrations of chemically synthesized surfactants for stability, posing food safety risks. Furthermore, single lipid systems are ill-suited to resist pH changes and digestive enzyme activity in the gastrointestinal environment, easily leading to premature release and degradation of curcumin in the stomach, limiting its targeted release effect in the gut. Pickering emulsions use natural nanoparticles instead of chemical surfactants, avoiding safety risks, but their protective effect on curcumin still needs improvement. Emulsion gels, as semi-solid systems combining the dispersion structure of emulsions and the three-dimensional network characteristics of gels, can lock oil droplets through the gel network, effectively isolating them from adverse environmental factors and protecting the active substance from damage, while simultaneously achieving targeted release in the gastrointestinal tract, making them a research hotspot in the field of curcumin delivery.

[0004] Tilapia is an important freshwater aquaculture species with a large-scale industry. However, current tilapia processing in my country is mainly focused on primary frozen fillets, resulting in a simple product structure, low added value, and insufficient proportion of deep-processed products, highlighting the urgent need for industrial transformation and upgrading. The myofibrillar protein (TMP) in the white flesh of tilapia's back accounts for more than 50% of the total protein. Its amino acid composition is balanced, meeting food protein standards, and it also possesses excellent emulsifying and gelling properties, making it an ideal raw material for constructing food-grade functional carriers. However, natural myofibrillar protein has inherent defects such as poor water solubility and high sensitivity to environmental factors like pH and ionic strength, severely limiting its large-scale application in functional food systems and hindering the high-value development of tilapia meat.

[0005] To improve the functional properties of myofibrillar proteins, various modification methods have been developed, including physical modification, chemical modification, enzymatic modification, and protein-polysaccharide complex modification. Physical modification is simple to operate and leaves no chemical residue, but its improvement on protein functional properties is limited, and over-treatment can easily lead to excessive protein denaturation. Chemical modification can effectively improve the solubility and emulsification of proteins, but the reaction conditions are difficult to control precisely, and it is easy to introduce chemical residues or generate harmful byproducts, posing food safety risks. Enzymatic modification has mild reaction conditions and high specificity, but its high cost makes it difficult to meet the needs of industrial applications. Protein-polysaccharide complex modification forms a complex between protein and polysaccharide through non-covalent interactions such as electrostatic interactions and hydrogen bonds, which can synergistically improve the functional properties of proteins and has no safety risks, making it a more ideal modification method.

[0006] In the prior art, patent CN120960445A discloses a myofibrillar protein-κ-carrageenan oligosaccharide complex and its preparation method and application. This technology prepares TMP / κCOS nanocomposites through a pH-driven method, effectively improving the water solubility and environmental stability of myofibrillar protein. This complex can be used to encapsulate curcumin, with an encapsulation efficiency of up to 76.76%, which improves the dispersibility and stability of curcumin to a certain extent. However, this nanocomposite system still has many shortcomings: the encapsulation efficiency of curcumin still needs to be further improved, the retention rate of curcumin during storage is insufficient, the resistance to environmental factors such as light and heat is limited, and the bioavailability of curcumin after oral administration is low, which cannot fully meet the application requirements of efficient delivery of curcumin, and also limits the further high-value utilization of tilapia myofibrillar protein.

[0007] In summary, existing curcumin delivery systems generally suffer from insufficient stability, limited targeted controlled-release capability, and low bioavailability. The high-value application of tilapia myofibrillar protein is also limited by the environmental sensitivity of the raw material itself and the performance bottlenecks of existing modified systems. While existing TMP / κCOS nanocomposites have improved the functional properties of myofibrillar protein to some extent and achieved initial curcumin encapsulation, they still suffer from insufficient encapsulation efficiency, limited environmental resistance, and low oral bioavailability. These limitations fail to fully meet the practical application requirements for efficient curcumin delivery and do not fully tap the application potential of tilapia myofibrillar protein. Therefore, developing a novel curcumin delivery system based on TMP / κCOS nanocomposites to further improve curcumin encapsulation efficiency, storage and environmental stability, and oral bioavailability, while simultaneously promoting the in-depth upgrading and high-value development of the tilapia processing industry, has become an urgent technical challenge. Summary of the Invention

[0008] In existing technologies, TMP / κCOS nanocomposites have limited encapsulation efficiency when encapsulating curcumin, failing to fully address the inherent defects of curcumin, such as poor photothermal stability and low oral bioavailability. Furthermore, traditional emulsion-gel preparations often require acid, alkali, enzyme, or ion induction, resulting in harsh reaction conditions that can easily lead to the loss of encapsulated active substances. Moreover, there is a lack of research on constructing efficient curcumin delivery systems by combining existing nanocomposites with specific oil phases, thus hindering the full realization of the nanocomposites' application potential. The application scenarios for tilapia deep processing still need to be expanded.

[0009] This invention aims to address the aforementioned deficiencies by providing a curcumin-encapsulated composite emulsion gel, its preparation method, and its applications. This achieves efficient encapsulation and stable delivery of curcumin, expands the application scenarios of TMP / κCOS nanocomposites, and realizes the high-value utilization of tilapia. To this end, this invention provides the following technical solution:

[0010] In a first aspect, the present invention provides a method for preparing a composite emulsion gel loaded with curcumin, the preparation method comprising the following steps: S1, a nanocomposite was prepared by combining tilapia myofibrillar protein with κ-carrageenan oligosaccharide; S2, using the nanocomposite as the aqueous phase, an oil phase containing dissolved curcumin is added, and the composite emulsion gel loaded with curcumin is obtained through a one-step high-speed shearing process.

[0011] Furthermore, in step S1 of the above preparation method, the nanocomposite is prepared by a pH-driven method, specifically including: preparing a tilapia myofibrillar protein solution with a concentration of 10-14 mg / mL and a κ-carrageenan oligosaccharide solution with a concentration of 3-5 mg / mL; adjusting the pH of the two solutions to 11-13 respectively and then performing hydration treatment; mixing the two hydrated solutions, adjusting the pH of the mixed system to 6.5-7.5, stirring until the system is stable, and then centrifuging to remove the precipitate to obtain the nanocomposite.

[0012] Furthermore, in step S1 of the above preparation method, the hydration treatment conditions are: hydration at 0~6℃ for 10~14h; the two hydrated solutions are mixed at a volume ratio of 1:1.

[0013] Furthermore, in step S2 of the above preparation method, the oil phase is selected from one of medium-chain triglycerides, flaxseed oil, and anchovy oil.

[0014] Furthermore, in step S2 of the above preparation method, the volume fraction of the oil phase in the composite emulsion gel is 0.6~0.75; the conditions for the high-speed shearing treatment are: shearing speed 20000~24000 r / min, treatment time 1~5 min, and treatment temperature 20~30℃.

[0015] Based on the above preparation method, a second aspect of the present invention provides a composite emulsion gel loaded with curcumin prepared by the above preparation method.

[0016] Furthermore, the composite emulsion gel is an oil-in-water emulsion filled gel containing tilapia myofibrillar protein, κ-carrageenan oligosaccharide, an oil phase, and curcumin loaded in the oil phase.

[0017] Thirdly, the present invention seeks protection for the use of the above-mentioned curcumin-encapsulated composite emulsion gel in the preparation of functional foods.

[0018] Furthermore, in the above applications, the functional food is a delivery-type food used to enhance the oral bioavailability of curcumin.

[0019] The present invention, "A composite emulsion gel encapsulating curcumin, its preparation method and application," has at least the following beneficial effects: This invention is based on the existing publicly available TMP / κCOS nanocomposite. By constructing an emulsion gel system with a specific oil phase, a higher efficiency of curcumin encapsulation can be achieved. The curcumin encapsulation rate can reach more than 90%, which is significantly higher than the encapsulation effect when using the nanocomposite alone, and can further improve the encapsulation efficiency of curcumin.

[0020] This emulsion-gel system can further improve the stability of curcumin. After long-term storage at 4℃ for 28 days, the curcumin retention rate can still reach more than 90%. After heating at 90℃ for 6 hours, the highest retention rate of curcumin can reach 83.86%, and after irradiation with ultraviolet light for 60 hours, the highest retention rate can reach 47.15%. Compared with simple nanocomposites, it can more effectively protect curcumin from degradation during processing and storage, and further improve the inherent defect of poor photothermal stability of curcumin.

[0021] Meanwhile, this system can significantly improve the in vitro digestibility of curcumin, reaching up to 44.49%. Compared with simple nanocomposites, it can more effectively improve the problem of low oral bioavailability of curcumin, ensuring its effective absorption in vivo. Furthermore, the preparation process of this invention is simple, requiring only a one-step high-speed shearing process based on existing nanocomposites, without the need for additional stringent induction conditions, thus avoiding the loss of active substances and facilitating large-scale application. It also expands the application scenarios of TMP / κCOS nanocomposites, providing a new pathway for the intensive processing of tilapia. Attached Figure Description

[0022] Figure 1 The appearance of TMP / κCOS emulsion gels prepared under different oil phase types and volume fractions.

[0023] Figure 2Rheological properties of TMP / κCOS emulsion gels prepared under different oil phase types and volume fractions are shown; where A~C represent the storage modulus (G') and loss modulus (G") of the emulsion gel as a function of angular frequency (0.1~10 rad / s); D~F represent the apparent viscosity of the emulsion gel as a function of shear rate (0.1~100 s⁻¹). -1 The changes in ).

[0024] Figure 3 The gel strength of TMP / κCOS emulsion gels prepared under different oil phase types and volume fractions.

[0025] Figure 4 Microscopic morphology images of TMP / κCOS emulsion gels prepared for different volume fractions of medium-chain triglycerides (MCT) observed under a laser confocal microscope; where the green area represents the FITC-stained protein / polysaccharide (TMP / κCOS) continuous phase, and the red area represents the Nile Red-stained oil phase.

[0026] Figure 5 Microscopic morphology of TMP / κCOS emulsion gels prepared with different volume fractions of linseed oil (FO) as observed under a laser confocal microscope.

[0027] Figure 6 Microscopic morphology of TMP / κCOS emulsion gels prepared with different volume fractions of anchovy oil (EJO) as observed under a laser confocal microscope.

[0028] Figure 7 Low-field nuclear magnetic resonance (LF-NMR) characterization results of water distribution in TMP / κCOS emulsion gels prepared under different oil phase types and volume fractions; where (A) is a bar chart showing the proportion of water content in different states in emulsion gels with different oil phase types and volume fractions, and P... 2b P represents strongly bound water. 21 Represents weakly bound water, P 22 P represents semi-free water. 23 The letter represents free water, and the letters are used to indicate statistical differences between different samples. (B), (C), and (D) are the lateral relaxation time (T2) distribution curves of emulsion gels with different volume fractions constructed from medium-chain triglycerides (MCT), flaxseed oil (FO), and anchovy oil (EJO), respectively.

[0029] Figure 8 Apparent long-term storage stability of TMP / κCOS emulsion gels prepared under different oil phase types and volume fractions.

[0030] Figure 9 The water-holding capacity of TMP / κCOS emulsion gels prepared under different oil phase types and volume fractions.

[0031] Figure 10 To assess the apparent long-term storage stability of TMP / κCOS emulsion gels loaded with curcumin prepared with different oil phases at a volume fraction of 0.7%.

[0032] Figure 11 The study investigated the changes in curcumin (CUR) retention during storage of TMP / κCOS emulsion gels loaded with curcumin prepared with different oil phases at a volume fraction of 0.7.

[0033] Figure 12 The study investigated the changes in curcumin (CUR) retention rate of TMP / κCOS emulsion gels loaded with curcumin prepared with different oil phases under UV irradiation at a volume fraction of 0.7.

[0034] Figure 13 The changes in curcumin (CUR) retention rate of TMP / κCOS emulsion gels loaded with curcumin prepared with different oil phases after heating are shown under the condition of 0.7% by volume.

[0035] Figure 14 To measure the free fatty acid (FFA) release rate of TMP / κCOS emulsion gels loaded with curcumin prepared with different oil phases under simulated small intestinal digestion conditions at a volume fraction of 0.7, the simple oil phases MCT-Oil, FO-Oil, and EJO-Oil were used as controls.

[0036] Figure 15 To investigate the bioaccessibility of CUR in TMP / κCOS emulsion gels loaded with curcumin prepared with different oil phases under a volume fraction of 0.7. Detailed Implementation

[0037] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0038] Unless otherwise specified in the examples, the methods or conditions described in the literature in this field or in accordance with the product instructions shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0039] Example 1: Preparation of TMP / κCOS emulsion gels with different oil phase types and volume fractions.

[0040] 1. Preparation of aqueous raw materials Nanocomplexes were prepared using a pH-driven method: Myofibrillar protein (TMP) was suspended in deionized water to prepare a TMP suspension with a concentration of 12 mg / mL. The pH was adjusted to 12 with 2 mol / L NaOH solution, and the solution was hydrated at 4°C for 12 h. Separately, κ-carrageenan oligosaccharide (κCOS) was suspended in deionized water to prepare a κCOS suspension with a mass fraction concentration of 4 mg / mL. The pH was adjusted to 12 with 2 mol / L NaOH solution, and the solution was hydrated at 4°C for 12 h. After hydration, the suspensions were allowed to return to room temperature. The two suspensions were then mixed at a volume ratio of 1:1 and magnetically stirred at 600 rpm for 60 min. The pH was then adjusted to 7.0 with 2 mol / L HCl solution, and magnetic stirring was continued for 120 min until the solution stabilized. The resulting mixture was centrifuged at 4000 rpm for 10 min to remove precipitates, yielding the myofibrillar protein / κ-carrageenan oligosaccharide nanocomplex, denoted as the TMP / κCOS complex.

[0041] 2. Preparation of Emulsion Gel Different types and volume fractions of oil phases were added to the aqueous phase. Specifically, three oil phases were selected: medium-chain triglycerides (MCT, representing medium-chain saturated fatty acid oil phase), flaxseed oil (FO, representing long-chain polyunsaturated fatty acid oil phase), and anchovy oil (EJO, representing ultra-long-chain polyunsaturated fatty acid oil phase). For each oil phase, four gradients of oil phase volume fraction φ were set: 0.2, 0.4, 0.6, 0.65, 0.7, and 0.75. Preliminary experimental results showed that when the oil phase volume fraction was 0.2 and 0.4, the samples prepared by all three oil phases had shear inhomogeneity problems, and therefore were not included in the effective sample range of this preparation. After the oil phases were added, the samples were homogenized for 2 min at 22000 r / min under 25℃ using a high-shear homogenizer to complete the preparation of emulsion gel samples with different parameters.

[0042] The morphology of each prepared sample after standing for 20 minutes is as follows: Figure 1 As shown, Figure 1 The appearance of TMP / κCOS emulsion gels prepared under different oil phase types and volume fractions is shown in the figures, with the oil phase type and volume fraction labeled respectively. All samples showed a uniform and stable state, without stratification or obvious precipitation of aqueous or oil phases. The sample prepared with the MCT oil phase was uniformly milky white, while the samples prepared with the FO and EJO oil phases were uniformly milky yellow.

[0043] Example 2: Characterization of emulsion gel systems with different oil phase types and volume fractions.

[0044] All emulsion gel samples prepared in Example 1 were subjected to the following 7 performance characterization tests in sequence, and all tests were repeated in triplicate: 1. Rheological property determination The MARSⅢ modular advanced rheometer was used for testing. A P35 rotor was selected, and the distance between the rotor and the sample stage was set to 1 mm. An appropriate amount of sample was placed on the sample stage and allowed to equilibrate for 3 minutes. The pressure bar was then lowered, and after the pressure bar stopped, excess sample was scraped off. For apparent viscosity determination, the test temperature was set to 25℃, and the shear rate range was 0.1~100 s⁻¹. -1 Record the apparent viscosity of the sample; frequency scanning measurement: set the test temperature to 25℃, the strain to 0.1% (within the linear viscoelastic region of the emulsion gel), the frequency scanning range to 0.1~10rad / s, and record the storage modulus (G') and loss modulus (G") of the sample.

[0045] 2. Gel strength determination The sample was cut into cylinders with a diameter of 3 cm and a height of 3 cm and placed at room temperature for 30 min. The gel strength was determined using a TA.XT plus C texture analyzer with a P / 0.5 probe. The pre-test speed and test speed were both 2.0 mm / s, the test speed was 0.5 mm / s, the post-test speed was 2.0 mm / s, the strain was 40%, and the trigger force was 5 g.

[0046] 3. Droplet size and zeta potential determination Droplet size was determined using a Winner 2309 laser particle size analyzer. 200 µL of sample was added to 500 mL of deionized water with a stirring speed of 2400 rpm. Testing began when the masking rate reached 9%. The refractive index of the oil phase was set to 1.45, and the refractive index of the aqueous phase to 1.33. The surface-weighted average diameter (D) of the sample was obtained. 3,2 ) and volume-weighted average diameter (D 4,3 Zeta potentials were measured using a Zeta potential analyzer, and the samples were diluted 100 times before testing to eliminate multiple scattering effects.

[0047] 4. Laser confocal microstructure observation The observation was performed using a STELLARIS 5 laser confocal scanning microscope. During sample preparation, 0.05 mg / mL FITC was added to the TMP / κCOS aqueous phase, and 0.05 mg / mL Nile Red was added to the oil phase. During testing, FITC was excited at a wavelength of 488 nm, and the emission light was collected at 518 nm to characterize the TMP / κCOS phase. Nile Red was excited at a wavelength of 552 nm, and the emission light was collected at 565 nm to characterize the oil phase.

[0048] 5. Measurement of Moisture State Distribution A low-field nuclear magnetic resonance analyzer (NMR) of type NMI20-060H-I was used to acquire signals using the Carr-Purcell-Meiboom-Gill (CPMG) pulse sequence. 10g of sample was placed in the NMR tube, and the probe was set to NIMI21-60H-I-60mm, the proton resonance frequency was 21MHz, the echo time was 0.02ms, the waiting time was 4000ms, the number of echoes was 16000, the number of scans was 16, and the test temperature was 32℃. The decay curve was fitted to obtain the transverse relaxation time (T2) distribution map and the corresponding peak area ratio.

[0049] 6. Storage stability test The prepared samples were placed into sample vials and stored at 4°C for 28 days. The condition of the samples was observed and recorded on days 1, 7, 14, 21, and 28.

[0050] 7. Water-holding capacity test The sample was stored at 25℃ for 2 days until it stabilized. 5.0 g of the sample was placed in a 15 mL plastic centrifuge tube and centrifuged at 8000 r / min for 10 min at room temperature. The precipitated layer was collected and weighed, and recorded as m. 总 The weight of the centrifuge tube is denoted as m. 皮 The water-holding capacity is calculated using the following formula: Water retention (%) = (m 总 -m 皮 () / mass of emulsion gel sample × 100 In the above formula, m 总 m represents the total weight (g) of the sample and centrifuge tube after the separation layer is discarded. 皮 The value is the weight (g) of the centrifuge tube.

[0051] All the above measurements were repeated three times. Graphs were created using Origin 2022 software, and one-way ANOVA and Duncan's test were performed using SPSS statistical software. p <0.05 indicates a significant difference. The experimental results are as follows: 1. Rheological properties (1) Frequency scanning analysis Frequency scanning can characterize the dynamic viscoelasticity of emulsion gels and reflect their network structure characteristics. Figure 2Figures A, C, and E illustrate the variations in storage modulus (G') and loss modulus (G") of TMP / κCOS emulsion gels with different oil phases and volume fractions as a function of angular frequency (0.1–10 rad / s). Throughout the entire frequency range, G' consistently exceeded G" for all samples, and the two did not overlap, indicating that the TMP / κCOS emulsion gels formed a stable three-dimensional network structure with good long-term storage stability. Under constant strain conditions, both G' and G" increased with frequency, suggesting that the system exhibited predominantly elastic response and solid-like mechanical properties within the tested frequency range.

[0052] As the oil phase volume fraction increased from 0.6 to 0.75, the formation of the oil droplet network at high oil phase volume fractions led to a significant increase in G', specifically in the order of 0.75 > 0.7 > 0.65 > 0.6. This indicates that the oil droplet spacing decreased, the interaction between droplets increased, and the oil droplets squeezed each other to form a continuous oil droplet network, which together with the protein-polysaccharide gel network constituted a composite network structure, thereby synergistically enhancing the elastic response of the gel.

[0053] When the oil phase content was 0.75%, the G' values ​​of the emulsion gels prepared with different oil phases showed a pattern of FO group > MCT group > EJO group, with storage moduli of 478 Pa, 385 Pa, and 367 Pa, respectively, at a frequency of 10 rad / s. The difference in G' values ​​indicates that the chain length and saturation of the oil phase jointly affect the elastic response of the emulsion gel. The FO group had the highest storage modulus, which is attributed to the longer carbon chains and higher unsaturation (linolenic acid C18:3) in FO, providing ample hydrophobic interaction sites for long-chain fatty acids. Multiple double bonds also impart a certain degree of flexibility to the molecules, facilitating the formation of a dense gel network with the TMP / κCOS complex. Although MCT is a saturated fatty acid with strong intermolecular forces, its shorter carbon chains (mainly C8~C12) result in weaker effective interactions with the TMP / κCOS complex compared to the FO group, leading to a weaker gel network strength. The EJO group had the lowest G' value, and its oil phase was also dominated by polyunsaturated fatty acids (rich in ultra-long-chain polyunsaturated fatty acids EPA and DHA), indicating that the effect of fatty acid chain length may be greater than that of saturation. In addition, the ultra-long carbon chains (C20~C22) of EPA and DHA in EJO may generate greater steric hindrance, which may reduce the interaction with the complex and hinder the formation of gel network, resulting in a relatively loose gel structure.

[0054] (2) Shear rate scan analysis Shear rate scanning can reveal flow behavior under large deformation. Figure 2 Figures B, D, and F illustrate the variation of apparent viscosity of TMP / κCOS emulsion gels with shear rate for different oil phases and volume fractions. (0.1–100 s⁻¹) -1Within the range, all samples exhibited typical shear-thinning behavior: viscosity decreased significantly with increasing shear rate, especially in the low shear rate region (0~20s). -1 The decrease is most dramatic in the high shear rate region (60~100s). -1 The friction gradually leveled out. This is because the shearing action disrupted the three-dimensional network structure between oil droplets, reducing the frictional resistance within the system.

[0055] In the low shear rate region (0~20s) -1 There was no significant ranking trend in viscosity among different oil phases. In the high shear rate region (60~100s),... -1 When the oil phase volume fraction was high (0.7, 0.75), the viscosity of the EJO group was significantly higher than that of the FO and MCT groups. This difference is related to the fatty acid chain length of the oil phase: EPA and DHA in EJO are ultra-long-chain polyunsaturated fatty acids, and their oil phase itself has a high viscosity, maintaining a large flow resistance under high shear; MCT is a medium-chain saturated fatty acid, with a lower oil phase viscosity and the lowest flow resistance under high shear; FO is in between. When the oil phase volume fraction was low (0.6, 0.65), the viscosity difference among the three types of oil phases in the high-shear region was not significant, which may be because the oil droplet spacing was larger, and the interaction between oil droplets was weakened under shear.

[0056] 2. Gel strength of emulsion gel Gel strength is an important indicator reflecting the ability of an emulsion gel to resist deformation, and it is closely related to the properties of the oil phase and the volume fraction of the oil phase. Figure 3 The gel strength of TMP / κCOS emulsion gels with different oil phase types and volume fractions is shown.

[0057] From the perspective of oil phase volume fraction, as the volume fraction increased from 0.6 to 0.7, the gel strength of all three groups of samples increased significantly. p <0.05): The gel strength of the MCT group increased from 7.52±2.33g to 19.76±1.06g, the FO group from 5.51±0.02g to 18.84±0.64g, and the EJO group from 3.52±0.01g to 16.93±0.23g. This trend is consistent with the result that the storage modulus increases with increasing volume fraction in the frequency scan, indicating that the oil droplets are more densely packed under a high oil phase volume fraction, and the overall mechanical properties of the gel are enhanced. When the volume fraction is further increased to 0.75, the gel strength of the MCT group did not change significantly compared with the volume fraction of 0.7 (19.13±1.06g), while the FO and EJO groups decreased to 17.79±0.28g and 15.90±0.07g, respectively. This may be due to the insufficient continuous phase caused by the excessively high oil phase ratio, resulting in local loosening of the network structure.

[0058] From the perspective of oil phase type, at volume fractions of 0.65 and 0.75, the gel strength showed the order of MCT group > FO group > EJO group. p <0.05), this ranking differs from the ranking of storage modulus in the frequency scan (FO>MCT>EJO), reflecting the destructive behavior of gel strength under large deformation. The MCT group has the highest gel strength, which is related to its shorter fatty acid chain length and the distribution characteristics of the complex on the oil droplet surface; the FO group has the strongest elastic response, but its hardness under large deformation is slightly lower than that of the MCT group; the EJO group has the lowest in both indicators. At a volume fraction of 0.7, there is no significant difference between the MCT and FO groups, and both are significantly higher than the EJO group; at a volume fraction of 0.6, the MCT group is significantly higher than the EJO group, but there is no significant difference between it and the FO group.

[0059] The above results indicate that the oil phase volume fraction affects the overall level of gel strength by regulating the oil droplet packing density, while the oil phase type determines the strength difference at the same volume fraction. Together, they determine the macroscopic mechanical behavior of the emulsion gel.

[0060] 3. Droplet size and Zeta potential Droplet size is a key parameter determining the structure of emulsion gel networks, among which D 3,2 (Average diameter of surface area) reflects the specific surface area of ​​the droplet, D 4,3 (Volume average diameter) is sensitive to large particles and can reflect the degree of oil droplet aggregation and the uniformity of particle size distribution. Table 1 shows the droplet size and Zeta potential of TMP / κCOS emulsion gels with different oil phases and volume fractions.

[0061] Table 1: Droplet size and Zeta potential of TMP / κCOS emulsion gels prepared under different oil phase types and volume fractions.

[0062] From the perspective of oil phase volume fraction, as the volume fraction increases from 0.6 to 0.7, the D of each oil phase sample... 4,3 Both showed a decreasing trend; when the volume fraction increased to 0.75, the D values ​​of the MCT group and the EJO group decreased. 4,3 The concentration of D increased slightly compared to 0.7, while the concentration of FO continued to decrease. This change is consistent with the trends in storage modulus and gel strength, indicating that oil droplets are more densely packed and the gel network is more compact at higher oil phase volume fractions, resulting in overall enhanced mechanical properties. Specifically, MCT and EJO droplets are more prone to extrusion deformation or multiphase distribution at higher volume fractions, leading to increased D... 4,3 The growth rate rebounded; however, FO, due to its strong affinity, was able to maintain a uniform particle size distribution.

[0063] From the perspective of oil phase type, at a volume fraction of 0.75, D 4,3showing the order of FO group (2.96 μm) < MCT group (5.25 μm) < EJO group (5.64 μm), which corresponds to the ranking of the storage modulus. The D values of the three groups of samples 3,2 have small differences (2.08~2.61 μm), indicating that the difference in storage modulus mainly originates from the aggregation degree of large oil droplets. In addition, D at a volume fraction of 0.6 4,3 is much larger than D 3,2 , indicating the presence of a large number of large droplets; at 0.75, the difference between the two is greatly reduced, which proves that the particle size distribution is more uniform at high volume fractions, and large droplets are effectively broken.

[0064] The potential measurement results show that within the same oil phase, the absolute value of the potential of the MCT group continues to increase significantly with the increase of the volume fraction, increasing from -13.10 mV to -22.77 mV, and the electrostatic stability increases steadily; although the FO and EJO groups have fluctuations, they still maintain a high absolute value at high volume fractions. Under the same volume fraction, different oil phases have little effect on the surface charge of the droplets, which is a common phenomenon in high internal phase emulsions.

[0065] 4. CLSM Microstructure The morphology and positional distribution of polysaccharides and oil phase in the emulsion gel can be observed by CLSM, and the results are shown in Figures 4-6 : the green area is the TMP / κCOS continuous phase stained by FITC, and the red area is the oil droplets stained by Nile Red. All samples present a structure with TMP / κCOS as the continuous phase and oil droplets as the dispersed phase. TMP / κCOS uniformly coats the surface of the oil droplets and forms a continuous gel network, and the oil droplets are independently dispersed in the continuous phase, indicating that the system is a typical oil-in-water emulsion-filled gel; green fluorescent spots exist inside some oil droplets, indicating that a small amount of aqueous phase is encapsulated in the oil droplets, forming a W / O / W multiple emulsion structure.

[0066] From the perspective of oil phase volume fraction, in the sample with a volume fraction of 0.6, the distribution and size of oil droplets are irregular, and there are many large oil droplets; as the volume fraction increases, the oil droplet size decreases, at high volume fractions, the oil droplet size tends to be uniform, the oil droplet accumulation is tighter, and the gel network structure is denser. From the perspective of oil phase type, at high volume fractions of 0.7 and 0.75, the droplet size shows the order of MCT group > EJO group > FO group, which corresponds to the previous experimental data, and this difference is related to the fatty acid chain length, saturation of the oil phase and the distribution of the complex on the oil droplet surface.

[0067] 5. Water Distribution and Relaxation Time Low-field nuclear magnetic resonance (LF-NMR) can be used to analyze the internal proton information of the sample and monitor the distribution and mobility of water in the gel structure. The results are shown in Table 2, Figure 7 . According to the relaxation time of hydrogen protons, the water in the emulsion gel can be divided into four categories: T 2b(0.1~10ms, strongly bound water), T 21 (10~50ms, weakly bound water), T 22 (50~200ms, fixed water), T 23 (500~10000ms, free water).

[0068] Table 2: Relaxation time of TMP / κCOS emulsion gel

[0069] It can be seen that all samples are mainly composed of immobilized water; no strongly bound water was detected in the MCT group, and no weakly bound water was detected in the FO and EJO groups. This difference is related to the length of the fatty acid chain in the oil phase and the cross-linking density of the gel network: the gel network cross-linking density of MCT is higher, and water molecules are more tightly bound to macromolecules; the long-chain unsaturated fatty acids of FO and EJO have stronger hydrophobic interactions with proteins.

[0070] Regarding the oil phase volume fraction, the MCT group had weakly bound water T 21 The duration of fluidity increased significantly with increasing volume fraction, and the mobility slightly improved; the FO and EJO groups showed strong bound water T 2b The temperature stabilized within 7-9 ms, with minimal influence from volume fraction; the three groups maintained a constant water T. 22 No significant changes were observed in any of the groups; the free water concentration in the MCT group increased with increasing volume fraction, while in the FO and EJO groups it peaked at 0.65 volume fraction and then decreased slightly. Regarding the oil phase type, the MCT system was dominated by weakly bound water, and its T... 22 T 23 All samples showed significantly longer relaxation times than the FO and EJO groups, with the corresponding relaxation time curves shifting to the right, indicating stronger water mobility. The gel networks of FO and EJO were more dense, resulting in more significant restriction of water molecule movement. Regarding the water content, all samples had more fixed water P... 22 The largest proportion (85-96%) is the core of water-holding capacity, and free water P 23 Secondly, the bound water proportion was the smallest. As the oil phase volume fraction increased from 0.6 to 0.75, the fixed water proportion significantly increased in all three groups, the free water proportion significantly decreased, and the bound water proportion changed relatively little. At a volume fraction of 0.75, the fixed water proportions showed the order MCT group > EJO group > FO group. The free water proportion in the MCT group was significantly lower than the other two groups, indicating that water is more easily bound in the MCT system, resulting in better physical stability.

[0071] 6. Storage stability In this experiment, TMP / κCOS emulsion gels with different oil phases (MCT, FO, EJO) and different volume fractions were prepared and stored at 4℃ for 28 days. Their morphological changes were monitored, and the results are as follows: Figure 8 As shown, the emulsion gel constructed by MCT is milky white, while those constructed by FO and EJO are uniformly milky yellow.

[0072] On day 1, all samples were homogeneous, with no stratification or significant precipitation of aqueous or oil phases, demonstrating the excellent emulsifying properties of TMP / κCOS. From day 7 onwards, all oil phase samples with a volume fraction of 0.6 showed stratification, a result consistent with previous NMR results. At a volume fraction of 0.6, the proportion of free water was higher, making it more prone to precipitation and stratification. Samples with volume fractions of 0.65, 0.7, and 0.75 maintained their original state during the 28-day storage period, showing no oil-water stratification, no oil phase precipitation, and no microbial contamination. The tightly packed oil droplets formed a "blocking" network, effectively binding free water and exhibiting excellent storage stability.

[0073] 7. Water-holding capacity analysis Water retention is an important indicator reflecting the density and physical stability of the emulsion gel network structure, and it reflects the gel's ability to retain water under external forces. The results are as follows: Figure 9 As shown.

[0074] As the oil phase volume fraction increased from 0.6 to 0.75, the water holding capacity of the MCT, FO, and EJO groups all increased significantly: the MCT group increased from 63.77±0.40% to 76.22±0.38%, the FO group from 67.90±0.14% to 79.61±0.51%, and the EJO group from 68.84±1.70% to 78.97±1.60%. This trend is consistent with the trend of increasing fixed water ratio with increasing volume fraction in NMR analysis. At the same time, the dense network formed by the TMP / κCOS complex effectively restricted water molecule migration and enhanced water holding capacity.

[0075] At a volume fraction of 0.75, the water-holding capacity followed the order FO group > EJO group > MCT group. This order differs from the order of gel strength and NMR-fixed water ratio, indicating that the three reflect different characteristics of the gel network. Water-holding capacity reflects the strength of the bond between water and the network. The long-chain polyunsaturated fatty acids in EJO and FO interact more strongly with the complex, resulting in a stronger bond between water molecules and making them less prone to loss under external forces.

[0076] In summary, the emulsion gel with a volume fraction of 0.7% exhibits the best performance in terms of elasticity, droplet size, particle size uniformity, and storage stability. Therefore, the emulsion gel with an oil phase volume fraction of 0.7% was selected as the optimal volume fraction for subsequent curcumin encapsulation and in vitro digestion studies.

[0077] Example 3: Stability evaluation of TMP / κCOS emulsion gel loaded with curcumin.

[0078] The foregoing examples have clarified the basic physicochemical properties of TMP / κCOS emulsion gels prepared from three oils. In this example, curcumin is further loaded into the TMP / κCOS emulsion gel during its preparation process to verify the encapsulation effect of the curcumin-loaded emulsion gel on curcumin and its stability under storage, light, and heat conditions.

[0079] 1. Sample preparation Experimental Samples: Curcumin (CUR) was added to medium-chain triglycerides (MCT), flaxseed oil (FO), and anchovy oil (EJO), respectively. The mixture was stirred continuously for 2 hours in the dark until the curcumin concentration in the oil phase reached 0.5 mg / mL. The dissolved oil phase was then transferred to a brown glass bottle and stored at 4°C in the dark. Using a TMP / κCOS nanocomposite solution (TMP concentration 12 mg / mL, κCOS concentration 4 mg / mL) as the aqueous phase, the above-mentioned curcumin-containing oil phase was added, controlling the oil phase volume fraction to 0.7%. After mixing the aqueous and oil phases, the mixture was sheared at 22000 r / min for 2 min using a high-shear homogenizer to prepare curcumin-encapsulated TMP / κCOS emulsion gels, denoted as CUR-MCT, CUR-FO, and CUR-EJO, respectively.

[0080] Control samples: The TMP / κCOS / CUR nanocomposite loaded with curcumin and the CUR blank control group were used as control samples. TMP / κCOS / CUR nanocomposite: The preparation method was as described in Example 1, "1. Preparation of Aqueous Raw Materials". After the step of "mixing the two suspensions at a volume ratio of 1:1", a 2 mg / mL anhydrous ethanol solution of CUR (prepared in advance in the dark) was slowly added to the mixture to achieve a final concentration of 0.2 mg / mL. Subsequent steps such as magnetic stirring and pH adjustment were the same. CUR blank control group: The 2 mg / mL anhydrous ethanol solution of CUR was diluted with ultrapure water to obtain a 0.2 mg / mL curcumin ethanol aqueous solution.

[0081] All samples from both the experimental and control groups were left to stand overnight at 4°C and then brought to room temperature before measurement.

[0082] 2. Determination of curcumin encapsulation efficiency Weigh 1 g of curcumin-encapsulated emulsion gel sample into a 15 mL centrifuge tube, add 10 mL of 95% ethanol (v / v), vortex for 5 min to extract curcumin, then centrifuge at 10000 r / min at room temperature for 10 min and collect the supernatant. Dilute the supernatant 10 times with anhydrous ethanol and measure the absorbance at 422 nm. Calculate the curcumin content with reference to the standard curve and dilution factor. Perform the measurement in triplicate for each sample and calculate the curcumin encapsulation efficiency (EE) using the following formula.

[0083] EE (%) = (m 荷 / m0)×100; In the above formula, EE represents the curcumin encapsulation efficiency (%), and m 荷 m0 represents the mass of curcumin loaded (mg), and m0 represents the mass of curcumin added (mg).

[0084] 3. Storage stability test The curcumin-encapsulated emulsion gel was placed into sample vials and stored at 4°C for 28 days. Samples were taken on days 1, 7, 14, 21, and 28 to determine the curcumin retention rate in the emulsion gel. The appearance of the emulsion gel was also recorded. The curcumin retention rate was calculated using the following formula.

[0085] Curcumin retention rate (%) = (mass of remaining curcumin / mass of added curcumin) × 100 4. Ultraviolet light stability determination The curcumin-encapsulated emulsion gel was treated under 365nm, 300W ultraviolet light for 60h. Samples were taken every 4h for the first 12h, and then every 8h thereafter for curcumin content determination. The TMP / κCOS / CUR nanocomposite and the CUR blank control group were used as controls, and the curcumin retention rate was calculated according to the method in step 3.

[0086] 5. Thermal stability determination The curcumin-encapsulated emulsion gel was heated in a 90°C water bath for 6 hours, and samples were taken every 1 hour to determine the curcumin content. The TMP / κCOS / CUR nanocomposite and the CUR blank control group were used as controls, and the curcumin retention rate was calculated according to the method in step 3.

[0087] All measurements were repeated three times. Graphs were generated using Origin 2022 software, and one-way ANOVA and Duncan's test were performed using SPSS statistical software. p <0.05 indicates a significant difference. The experimental results are as follows: 1. Curcumin encapsulation efficiency Encapsulation efficiency of curcumin is one of the core indicators for evaluating the performance of this carrier, directly determining the system's protective effect on active substances and delivery efficiency. The encapsulation efficiency test results are shown in Table 3.

[0088] Table 3: Encapsulation efficiency of curcumin in different oil phases of TMP / κCOS emulsion gel

[0089] Note: Different letters indicate significant differences. p <0.05).

[0090] As shown in Table 3, the curcumin encapsulation efficiency of the three emulsion gels was significantly higher. p <0.05) higher than MP / κCOS / CUR nanocomposite (76.76±3.90%). Among them, CUR-MCT had the highest encapsulation efficiency, followed by CUR-FO and CUR-EJO. Analysis shows that in the emulsion gel system, curcumin can be effectively encapsulated in the hydrophobic core of the oil phase, and the three-dimensional network structure formed by the gel can fix the oil droplets, restrict the migration and aggregation of oil droplets, and reduce the loss of curcumin during the preparation process. In contrast, in the nanocomposite system, curcumin is only loaded inside the composite network through hydrophobic interactions, without the protection of the hydrophobic microenvironment of the oil phase. Some curcumin is easily lost during processing, so the encapsulation efficiency is lower. The differences in encapsulation efficiency between different oil phases are directly related to the differences in hydrophobic interactions caused by the fatty acid chain structure of the oil phase: MCT, a medium-chain saturated triglyceride, has a simple molecular structure and low polarity, resulting in stronger hydrophobic interactions with curcumin and thus facilitating the stable retention of curcumin in the oil phase; FO and EJO, rich in long-chain polyunsaturated fatty acids, have more complex molecular structures and relatively weaker hydrophobic encapsulation and retention capabilities for curcumin. These results indicate that the introduction of the oil phase can significantly improve the encapsulation efficiency of curcumin.

[0091] 2. Storage stability All three curcumin-encapsulated emulsion gels initially exhibited a uniform yellow color. After storage at 4°C in the dark for 28 days, the apparent results were as follows: Figure 10 As shown, none of the three emulsion gels exhibited oil leakage, no color fading was observed, and the gel morphology remained intact without layering or demulsification. The changes in curcumin retention during storage are shown below. Figure 11 As shown, the curcumin retention rates of all samples decreased with prolonged storage time, but the rate of decrease differed significantly. After 28 days of storage, the retention rates of CUR-MCT were 93.27±1.00%, CUR-EJO was 91.43±1.56%, and CUR-FO was 90.29±1.03%, all higher than those of the TMP / κCOS / CUR nanocomposite (83.85±1.63%) and the CUR blank control group (79.04±0.34%). The overall trend was: emulsion gel group > nanocomposite group > CUR blank control group. Analysis revealed that the protective effect of the emulsion gel on curcumin stems from a dual stabilization mechanism: the TMP / κCOS three-dimensional gel network acts as a physical barrier, hindering the transfer of oxygen and free radicals; the oil phase provides a hydrophobic microenvironment for curcumin, preventing direct exposure to the aqueous phase; and the stabilizing effect of the interface layer further maintains the oil droplet structure, delaying the oxidative degradation of curcumin. CUR-MCT has higher gel strength and a denser network structure. MCT is a saturated medium-chain fatty acid, which has better oxidative stability than FO and EJO, which are rich in polyunsaturated fatty acids. It can effectively avoid the accelerated degradation of curcumin caused by lipid oxidation, thus resulting in the highest retention rate.

[0092] 3. UV stability The test results for UV stability are as follows: Figure 12 As shown, after 60 hours of irradiation, the curcumin retention rates of each sample were ranked as follows: CUR-MCT (47.15±2.18%) > CUR-FO (42.99±1.73%) > CUR-EJO (25.14±1.33%) > TMP / κCOS / CUR (6.68±0.66%) > CUR blank control group (1.92±0.21%). Free curcumin degraded extremely rapidly under UV irradiation, with the retention rate dropping to 42.21±2.16% after 4 hours and only 1.92±0.21% after 60 hours. Although the TMP / κCOS / CUR nanocomposite had some protective effect, its retention rate after 60 hours was only 6.68±0.66%, far lower than that of the emulsion gel group. The protective effect of the emulsion gel is significant because curcumin encapsulated in the internal oil phase separates from the aqueous phase. The dense interface layer formed by the TMP / κCOS complex on the surface of the oil droplets effectively absorbs or scatters some ultraviolet light, reducing the light exposure intensity of curcumin. Simultaneously, the high oil phase volume fraction causes the oil droplets to pack tightly, extending the penetration path of ultraviolet light through the gel network and further weakening the radiation energy. Among the three emulsion gels, CUR-EJO showed a significantly faster degradation rate after 20 hours. This is because its rich unsaturated fatty acids readily undergo photo-oxidation under ultraviolet light irradiation, and the resulting free radicals react with curcumin, consuming curcumin molecules. Therefore, its retention rate is significantly lower than that of the MCT group.

[0093] 4. Thermal stability The test results of thermal stability are as follows Figure 13As shown, after heating at 90℃ for 6 hours, the curcumin retention rates of each sample were ranked as follows: CUR-MCT (83.86±1.24%) > CUR-EJO (75.59±0.33%) > CUR-FO (63.44±0.85%) > TMP / κCOS / CUR (9.81±0.94%) > CUR blank control group (8.44±0.57%). Consistent with the storage and photostability trends, the emulsion gel showed the best thermal protection effect for curcumin. Among them, the thermal stability of the CUR blank control group was extremely poor, with the retention rate dropping to 22.51±0.74% after heating for 1 hour and only 8.44±0.57% after 6 hours. Under high temperature, the non-covalent interactions of the proteins in the TMP / κCOS / CUR nanocomposite were disrupted, and the complex structure underwent irreversible unfolding, resulting in a retention rate of only 9.81±0.94% after 6 hours, which was far lower than that of the emulsion gel group. Among the three emulsion gels, CUR-MCT showed the highest retention rate, which is related to the dominant thermal oxidation mechanism in different oil phases: polyunsaturated fatty acids are prone to thermal oxidation at high temperatures, generating a large number of lipid peroxide free radicals. Curcumin, as a free radical scavenger, terminates the chain reaction by absorbing free radicals. When the free radical generation rate exceeds the scavenging capacity of curcumin, the curcumin molecules themselves are largely consumed. Therefore, the retention rates of the FO and EJO groups were lower than those of the MCT group. The results also indicate that under the experimental conditions, prolonged UV irradiation has a stronger degradation effect on curcumin than high-temperature heating treatment at 90℃.

[0094] Example 4: In vitro digestion characteristics of TMP / κCOS emulsion gel loaded with curcumin.

[0095] This embodiment further clarifies the digestive behavior of the three emulsion gels and the bioavailability of curcumin through an in vitro simulated digestion experiment.

[0096] 1. Construction of a simulated in vitro digestion model and determination of free fatty acids This experiment simulates only the in vitro digestion process in the stomach and small intestine. The pH of the digestive solution was adjusted using 0.5 mol / L NaOH and 1 mol / L HCl, and the rate of fat digestion was characterized by the release rate of free fatty acids (FFA).

[0097] The experimental samples were CUR-MCT, CUR-FO, and CUR-EJO prepared according to Example 3, with an oil phase volume fraction of 0.7 and an initial curcumin concentration of 0.5 mg / mL. A blank control of digestion solution without samples was also set up to subtract background acidity.

[0098] Simulated gastric digestion stage: 10g of sample was mixed with 10mL of simulated gastric juice containing pepsin (3.2mg / mL) and NaCl (2mg / mL), respectively. The pH was adjusted to 2.8, and the mixture was shaken at 37℃ for 1h to complete the gastric digestion simulation.

[0099] Simulated small intestinal digestion stage: 20g of the sample after gastric digestion was taken, and 20mL of simulated small intestinal fluid containing NaCl (120mmol / L), CaCl2 (10mmol / L), bile salts (5mg / mL), lipase (3.2mg / mL), and pancreatic enzyme (2.4mg / mL) was added. The pH was adjusted to 7.0 with 1M NaOH standard solution and recorded as the zero point. The mixture was kept at 37℃ with shaking for 2h to simulate small intestinal digestion. During digestion, the pH-stat method was used, and 0.25M NaOH standard solution was continuously added to maintain the pH of the system at 7.0. The amount of NaOH solution consumed at 20, 40, 60, 80, 100, and 120 min was recorded. The amount of FFA released was calculated according to the following formula to evaluate the degree of fat hydrolysis.

[0100]

[0101] In the formula, V NaOH The volume (L) of NaOH solution added during 120 min of digestion in the small intestine; C NaOH M represents the molar concentration (mol / L) of the NaOH solution. Lipid m represents the relative molecular weight of the fat; Lipid It is the weight (g) of fat during the digestion process.

[0102] 2. Droplet size and zeta potential determination Samples were taken after each digestion stage, and the digestate was diluted 100-fold to avoid multiple scattering effects. Droplet size and zeta potential were measured separately. Droplet size: Measured using a laser particle size analyzer. 200µL of sample was added to 500mL of deionized water, and the rotation speed was maintained at 2400r / min. Testing began when the masking rate reached 9%. The refractive index of the oil phase was set to 1.45, and the refractive index of the water phase to 1.33. The surface-weighted average diameter (D) was used as the measurement. 3,2 ) and volume-weighted average diameter (D 4,3 () indicates the droplet size.

[0103] Zeta potential: Measured using a Zeta potential analyzer. Before testing, the sample is diluted 100 times with deionized water to eliminate interference from multiple scattering and ensure detection accuracy.

[0104] 3. Determination of the bioavailability of curcumin After small intestinal digestion, the system was transferred to a 50 mL centrifuge tube, and the enzymes were inactivated by boiling water. The tube was then centrifuged at 4 °C and 10,000 rpm for 30 min. The centrifuged sample separated into three phases. 5 mL of the middle micelle phase was extracted by vortexing in 20 mL of 95% ethanol, followed by centrifugation. The absorbance was measured at 422 nm, and the curcumin concentration was calculated using a standard curve. Bioavailability was then calculated using the following formula.

[0105]

[0106] Wherein, C1 is the concentration of curcumin in the mixed micelle phase (mg / mL); C2 is the concentration of curcumin in the original emulsion gel (mg / mL).

[0107] All measurements were repeated three times. Graphs were generated using Origin 2022 software, and one-way ANOVA and Duncan's test were performed using SPSS statistical software. p <0.05 indicates a significant difference. The experimental results are as follows: 1. Free fatty acid release characteristics The test results of FFA release rate are as follows: Figure 14 As shown, the FFA release rate of all samples increased with the extension of digestion time, and the release rate showed a trend of being fast at first and then slow. The release was faster in the first 60 minutes and gradually slowed down in the next 60 minutes. This kinetic characteristic is consistent with the general law of lipid digestion.

[0108] After 120 min of digestion, the FFA release rates of the three emulsion gels were ranked as follows: CUR-MCT (52.20±0.37%) > CUR-FO (26.82±0.63%) > CUR-EJO (16.03±0.18%). Meanwhile, the FFA release amounts of all three emulsion gels were significantly higher than those of their corresponding pure oil phases. The release rates of the pure oil phases were MCT-Oil (36.21±0.56%), FO-Oil (18.05±0.17%), and EJO-Oil (10.04±0.31%), respectively. CUR-MCT showed a 44.2% increase compared to the pure oil phase, CUR-FO a 48.1% increase, and CUR-EJO a 60.0% increase.

[0109] Analysis shows that the chain length and degree of unsaturation of fatty acids in the oil phase are the core factors determining the release rate of FFA: MCT is a medium-chain saturated fatty acid with a short carbon chain and strong hydrophilicity, making it more easily bound by pancreatic lipase and resulting in the fastest hydrolysis rate; FO is a long-chain polyunsaturated fatty acid with a relatively long carbon chain and strong hydrophobicity, resulting in the second fastest hydrolysis rate; EJO is an ultra-long-chain polyunsaturated fatty acid with the longest carbon chain and the greatest steric hindrance, resulting in the slowest hydrolysis rate. Furthermore, its high oxidation sensitivity means that the free radicals generated during digestion will inhibit lipase activity, further reducing hydrolysis efficiency.

[0110] The promoting effect of emulsion gel stems from the following: high-speed shearing disperses the oil phase into fine and uniform droplets, increasing the total surface area of ​​the oil droplets and providing more binding sites for lipases; simultaneously, during gastric digestion, the gel network can be partially hydrolyzed by pepsin, gradually exposing the encapsulated oil droplets, which is beneficial for subsequent enzymatic digestion; the antioxidant activity of curcumin can inhibit the oxidation of polyunsaturated fatty acids, reducing the inhibition of lipases by oxidation products. For the EJO group, which is the most oxidatively sensitive, the promoting effect of emulsion gel on the release of FFA is the most significant.

[0111] 2. Changes in droplet size and potential during digestion The changes in droplet size and potential during digestion are shown in Table 4: Table 4: Particle size and potential during digestion of CUR-TMP / κCOS emulsion gels with different oil phases

[0112] Note: Data are mean ± standard deviation (n=3). Uppercase letters indicate significant differences between different digestion stages of the same oil phase, and lowercase letters indicate significant differences within the same digestion stage. p <0.05).

[0113] Before digestion, the droplet size D of the three emulsion gels 4,3 The range is 2.21~3.21μm, and the absolute value of the Zeta potential is greater than 20mV, indicating that the system has good electrostatic stability.

[0114] After entering the gastric digestion stage (pH 2.8), the droplet size of all samples increased significantly. p <0.05): MCT group D 4,3 The droplet zeta potential increased from 2.79 μm to 5.18 μm, from 3.21 μm to 4.46 μm in the FO group, and from 2.21 μm to 3.56 μm in the EJO group. Simultaneously, the absolute value of the zeta potential decreased in all groups, with the largest decrease observed in the EJO group, from -25.57 ± 1.76 mV to -13.73 ± 1.56 mV. This is because under acidic conditions, the amino groups of the interfacial proteins undergo protonation, weakening the electrostatic repulsion and causing droplet flocculation. Simultaneously, pepsin hydrolyzes the interfacial protein membrane, disrupting the interfacial structure and promoting droplet fusion.

[0115] After entering the small intestine digestion stage (pH 7.0), the droplet size is smaller than that in the stomach stage: MCT group D 4,3 The zeta potential decreased to 3.91 μm in the FO group, 2.39 μm in the FO group, and 3.23 μm in the EJO group; at the same time, the absolute value of the zeta potential increased significantly. p<0.05), the values ​​increased to -31.53±1.20 mV in the MCT group, -35.67±1.65 mV in the FO group, and -42.30±1.71 mV in the EJO group. This is because the FFA produced by lipid hydrolysis deprotonates at neutral pH, adsorbs onto the surface of oil droplets, and increases the negative charge density. At the same time, the emulsification effect of bile salts further disperses large droplets into smaller droplets.

[0116] In summary, TMP / κCOS emulsion gels exhibit pH-dependent structural evolution during digestion: flocculation occurs in the gastric stage, with increased droplet size and decreased negative charge; dispersion occurs in the small intestine stage, with decreased droplet size and significantly increased negative charge.

[0117] 3. Bioavailability of curcumin Results of bioaccessibility testing, such as Figure 15 As shown, the bioavailability of curcumin in the three emulsion gels was ranked as follows: CUR-MCT (44.49±1.63%) > CUR-FO (27.92±1.32%) > CUR-EJO (20.27±1.21%), with significant differences. p <0.05), this ranking is completely consistent with the ranking of FFA release rate, indicating that the bioavailability of curcumin is positively correlated with the degree of hydrolysis of lipids.

[0118] Analysis shows that during the small intestine digestion stage, the products of lipid hydrolysis are the main components of mixed micelles. The higher the FFA release rate, the greater the amount of mixed micelles formed, which can solubilize and transport curcumin released from lipid droplets to intestinal epithelial cells, thus increasing the bioavailability of curcumin. MCT has a fast hydrolysis rate, rapidly generating a large number of mixed micelles, promoting the transfer and solubilization of curcumin, thus having the highest bioavailability. FO has the second fastest hydrolysis rate and the next lowest bioavailability. EJO has the slowest hydrolysis rate, resulting in insufficient mixed micelle formation, and its oxidation products interfere with micelle formation, thus having the lowest bioavailability.

[0119] The embodiments described above are only some, not all, of the embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art through related deductions and substitutions based on the inventive concept, without inventive effort, are within the scope of protection of the present invention.

Claims

1. A method for preparing a composite emulsion gel loaded with curcumin, characterized in that, Includes the following steps: S1, a nanocomposite was prepared by combining tilapia myofibrillar protein with κ-carrageenan oligosaccharide; S2, using the nanocomposite as the aqueous phase, an oil phase containing dissolved curcumin is added, and the composite emulsion gel loaded with curcumin is obtained through a one-step high-speed shearing process.

2. The preparation method according to claim 1, characterized in that, The nanocomposite was prepared by a pH-driven method, specifically comprising: preparing a tilapia myofibrillar protein solution with a concentration of 10-14 mg / mL and a κ-carrageenan oligosaccharide solution with a concentration of 3-5 mg / mL; adjusting the pH of the two solutions to 11-13 respectively and then performing hydration treatment; mixing the two hydrated solutions, adjusting the pH of the mixed system to 6.5-7.5, stirring until the system is stable, and then centrifuging to remove the precipitate to obtain the nanocomposite.

3. The preparation method according to claim 2, characterized in that, The hydration treatment conditions are: hydration at 0~6℃ for 10~14h; the two hydrated solutions are mixed at a volume ratio of 1:

1.

4. The preparation method according to claim 1, characterized in that, The oil phase is selected from one of the following: medium-chain triglycerides, flaxseed oil, and anchovy oil.

5. The preparation method according to claim 4, characterized in that, The oil phase has a volume fraction of 0.6-0.75 in the composite emulsion gel; the conditions for the high-speed shearing treatment are: shearing speed 20000-24000 r / min, treatment time 1-5 min, and treatment temperature 20-30℃.

6. A composite emulsion gel encapsulating curcumin, characterized in that, The composite emulsion gel is prepared by the preparation method according to any one of claims 1 to 5.

7. The composite emulsion gel according to claim 6, characterized in that, The composite emulsion gel is an oil-in-water emulsion filled gel containing tilapia myofibrillar protein, κ-carrageenan oligosaccharide, an oil phase, and curcumin loaded in the oil phase.

8. The application of the curcumin-encapsulated composite emulsion gel according to any one of claims 6 to 7 in the preparation of functional foods.

9. The application according to claim 8, characterized in that, The functional food is a delivery food designed to enhance the oral bioavailability of curcumin.

Citation Information

Patent Citations

  • Myofibrillar protein-kappa-carrageenan oligosaccharide compound as well as preparation method and application thereof

    CN120960445A